Pemberdayaan Masyarakat di Sekitar Cagar Budaya Melalui Pameran Museum - Sektiadi Sektiadi; Djaliati Sri Nugrahani (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
One of the eﬀorts to utilize the cultural heritage is to make it as a source of inspiration. In this case, the cultural heritage of Sojiwan Temple is used as an inspiration for the development of surrounding communities. People are encouraged to take advantage of the existence of the temple, namely by using it as a source of design inspiration cloth motif which later developed into batik craft. Te next step, crafters need to be presented directly to the batik community, both designers, manufacturers, and consumers. Terefore, it is necessary to do the exhibition with the need for the resulting batik gets appreciation from the wider audience. Batik exhibition is done by museum exhibition model, which has specifcation especially in delivery of story, or object as part of showing ideas. Te exhibition was held at the UGM Museum to reach out to people who have not been in direct contact with the craftsmen, the batik community and academics.